Preferences for groundnut products among urban residents in Ghana. (28th August 2017) - Meng, Ting; Florkowski, Wojciech J; Klepacka, Anna M; Sarpong, Daniel B; Resurreccion, Anna V A; Chinnan, Manjeet S; Ekielski, Adam
Abstract: BACKGROUND: The present study identifies factors influencing preferences for common groundnut products using information about product perceptions from residents in Ghana's cities collected in 2011. In Ghana, domestically produced groundnuts, processed into a variety of groundnut products, are a vital source of protein and other nutrients. RESULTS: Response summaries provide insights about the eating frequency of various products, whereas a bivariate ordered probit model identifies factors influencing preferences for groundnut paste and roasted groundnuts. Attributes such as taste, protein content and healthfulness are important for roasted groundnuts, whereas aroma, taste and protein content are associated with a preference for groundnut paste. Large households prefer paste, whereas the less educated and those from households with children prefer roasted groundnuts. Adding a child (4–12 years old) increases probability of 'liking very much' roasted groundnuts and an additional adult at home changes that probability regarding groundnut paste. College‐educated consumers prefer groundnut paste less than those with less education. Consumers from Tamale and Takoradi prefer roasted groundnuts and groundnut paste more than Accra households. CONCLUSIONS: Taste and protein content are attributes of groundnut paste and roasted groundnuts preferred by consumers. Location is a significant factor shaping preference for roasted groundnuts and groundnut paste. © 2017 Society of Chemical Industry